The business case for corporate social responsibility (CSR) is good business: A comparative analysis of CSR practices in the South African and Australian banking sectors - Machine, Abigail (Department of Commercial Law, 2015)
A focus of the study will be on the South African banking sector, comparing it with the CSR practices of Australian banking sector. The reason for this comparative analysis stems from the similarities that are prevalent between the two countries, although they have different designations, with one country as a developing country and the other as a developed country respectively. Both countries were once colonies. Australia was ruled by British and South Africa was ruled by Dutch and British. Both countries' financial sectors are well regulated and developed. Similar rules regarding disclosing information are applied in both countries' listed companies. The listed companies in both countries are required to disclose their social and environmental information in addition to their financial information